Pan: The Search for Sponsors - Unknown (Trinidad Guardian)
The steelband festival Pan is Beautiful VIII is over but the critics suggest that it was not an overwhelming success. The last three editions of the festival have landed the organizers in the red and the format sorely needs a drastic restructuring. Pan Trinbago recognises the need to host these events but the costs are too great and corporate sponsorship is dwindling.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Music festivals -- Trinidad and Tobago; Corporate sponsorship -- Trinidad and Tobago